Kajian tentang Kemungkinan Pemanfaatan Bahan Serat Ijuk sebagai Bahan Penyerap Suara Ramah Lingkungan - Zulfian, Zulfian; Sajidin, Muhammad (Jurnal Rekayasa Kimia & Lingkungan, 2009)
The probability of application of palm fibre from arenga pinnata appear as best treatment for sound absorption material which can be used in controlling noise. The objective of this study is to determine sound absorption coefficient value of palm fibre through a testing the absorbent material, by applying sabine reverberation time formulation in reverberation chamber at Thermal and acoustics laboratory Syiah Kuala University. Result of this study show that sound absorption coefficient value is obtained 0.97, at 2000 Hz. Whereas thickness of material 20 cm with density of 150 kg/m3. Addition of density can increase sound absorption coefficient value in frequency range 1/3 octave. Proven that a comparison palm fibre and artificial material and consequently palm give better quality values because it economic value and friendly environment.Keywords: palm fiber, reverberation chamber, sound absorption coefficient